A külföldi tőke szerepe és térbeli terjedése Magyarországon - Nagy, Gábor (Tér és Társadalom, 1995)
The direct inward investments mean one of the most important chances for Hungary for an economic catching up. The incoming capital is not of credit type, it stimulates home investments. The implementation of the specific projects may have employment consequences touching whole regions. They may bring novelties for the Hungarian units usually all in technical, technological, management, marketing, monitoring and quality respects, bringing developed Western productive and sales methods close at hand. Combining these with the Hungarian characteristics, the productivity of the Hungarian economic sectors can be raised to a higher levei. Such a form of economic co-operation can open the Eastern and Western markets for home-made products, increasing the possibilities for export. The appearance of the direct inward investments can provide a chance for a region for catching up, so in the study we focused mainly on the spatial distribution, penetration of the capital both in space and settlement hierarchy. In our work we were the first to attempt to divide the past period of time into sections by the behaviour of the foreign capital. We examined, by these sections, the changes taking place in the sectoral distribution of the joint ventures, the transitions that could be registered in the decision on the corporate form. We examined the origin of the incoming capital by country of origin, within this we tried to highlight the settlement preferences of the specific investing countries within Hungary. We tried to follow the change in the rate of foreign capital in the founded joint ventures during the Whole period, within this we paid special attention to the 100 % foreign owned or foreign majority businesses. The most significant part of the study tried to trace several dimensions of the spatial spreading of the joint ventures. Partly we were seeking the differences at the levei of the big regions and counties, partly we tried to make a distinction between the capacities of the levels of the settlement hierarchy. During the work, on the one hand, we categorised regions, counties and small regions with similar development patterns, on the other hand, we delimited the active and passive regions within Hungary (partly irrespective of counties and regions) and tried to introduce the investment types, behaviours typical of the region. In the last part we tried to show the chances for the regional policy in improving the conditions for the reception and functioning ,of the foreign capital. We came to the conclusion that state participation is still inevitable in the formation or alteration of the images of some regions.